2020
DOI: 10.5812/semj.96311
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Knowledge and Stigma Among the General Population in the Southeast of Iran

Abstract: Background: HIV-related stigma is a barrier to effective HIV responses among people living with HIV (PLHIV). Objectives: The current study aimed at measuring HIV-related stigma, and its associated factors among the general population in the Southeast of Iran. Methods: The current cross-sectional study was conducted on a convenience sample of 900 individuals in Kerman, Southeast of Iran, from July to September 2016. Data was collected using a self-administered questionnaire, including (I) demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Stigma and discrimination greatly affects the quality of life of PLWH, their family members and the healthcare providers who work with them (8,10,(23)(24)(25)(26)(27). People who experienced stigma face loss of income or job, isolation from communities, and inability to participate as a productive member of society (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma and discrimination greatly affects the quality of life of PLWH, their family members and the healthcare providers who work with them (8,10,(23)(24)(25)(26)(27). People who experienced stigma face loss of income or job, isolation from communities, and inability to participate as a productive member of society (28).…”
Section: Introductionmentioning
confidence: 99%
“…People who experienced stigma face loss of income or job, isolation from communities, and inability to participate as a productive member of society (28). Stigma is a barrier of good ART adherence which accelerates disease progression (23,(29)(30)(31)(32). It increases the risk of mental health problems (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…14,15,[17][18][19][20][21][22] Discrimination greatly affects the quality of life of PLWHA, their family members, and the healthcare providers who work with them. 8,10,[23][24][25][26][27] People who experienced discrimination face loss of income or job, isolation from communities, and inability to participate as a productive member of society. 28 Moreover, it is a barrier for ART adherence which accelerates disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amount of HIV/AIDS- related stigma and discrimination in this project has been reported elsewhere. 9 The future study is suggested to assess the validity and reliability of the scale in different samples. Research is also required to develop and validate stigmatizing and discriminatory attitudes of community toward family with a positive HIV-member.…”
Section: Discussionmentioning
confidence: 99%
“…With the onset of the HIV/AIDS epidemic, fear, stigma and discrimination were also identified as important barriers to an effective response to HIV. 7 The Joint United Nations Program on HIV/AIDS (UNAIDS) 8 defines HIV-related stigma as “a process of devaluation of people living with or associating with HIV and AIDS.” 9 There are 2 types of stigmas: internal stigma refers to the shame and expectation of discrimination that prevents people from talking about their experiences and stops them seeking help. External stigma refers to the experience of unfair treatment by others.…”
Section: Introductionmentioning
confidence: 99%